Insomnio como síntoma precoz en enfermedad de Creutzfeldt-Jakob esporádica: presentación de 3 casos - Díaz S., Mario; Zúñiga V., Carlos; Salinas C., Pablo; González R., Pablo; Aguilera O., Ledda (Revista Hospital Clínico Universidad de Chile, 2014)
In Chile a high incidence of Creutzfeldt – Jakob disease (CJD) has described. Insomnia is a symptom poorly studied in this disease, probably masked by the severity of other alterations. It contrasts with fatal familiar insomnia (IFF), another prionic disease with predominant involvement of thalamus, in which insomnia is a key symptom. We present three patients with clinical features and images compatible with sporadic CJD. All of them begun with severe and progressive insomnia, which preceded the final diagnosis by several months; this was associated with nocturnal psychomotor agitation and hypnagogic hallucinations. All patients died due to complications from severe dementia. Polysomnography was performed in one of the patients, which showed severe disturbance in sleep architecture with a predominance of light sleep, low sleep efficiency caused by large number of awakenings; absence of sleep spindles, vertex waves, and K complexes. In all cases caudate nucleus, thalamus, putamen and brain cortex sowed hyperintensities on T2 and diffusion weigthed brain MRI. Discussion: Insomnia was an important and early symptom in our patients with CJD. Associated with motor agitation, hallucinations, and one of them showed significant disturbance in the sleep architecture, with no spindles and vertex waves; findings also typically described in IFF. Probably the involvement of thalamic structures is a common pathophysiological pathway between these two diseases.